Thursday, February 13, 2025

23.5 - Solved Examples on Integration by Substitution

In the previous section, we saw some standard integrals of trigonometric functions. We saw some solved examples also. In this section, we will see a few more solved examples.

Solved example 23.7
Find the following integrals:
(i) $\small{\int{\left[(4x+2) \sqrt{x^2 + x + 1} \right]dx}}$

(ii) $\small{\int{\left[\frac{1}{1\,-\, \tan x} \right]dx}}$

(iii) $\small{\int{\left[\frac{1}{1\,+\, \cot x} \right]dx}}$

(iv) $\small{\int{\left[\frac{1}{x\,+\, x \log x} \right]dx}}$

Solution:
Part (i):
1. The derivative of (x2+x+1) is 2x+1.
• So we put u = x2+x+1
⇒ $\small{\frac{du}{dx}~=~2x\,+\,1}$
⇒ (2x+1)dx = du

2. So we want:
$\small{\int{\left[(4x+2) \sqrt{x^2 + x + 1} \right]dx}~=~\int{\left[2 \sqrt{u} \right]du}}$

• This integration can be done as shown below:

$\small{\begin{array}{ll} {~\color{magenta}    1    }    &{{}}    &{\int{\left[2 \sqrt{u}\right] \, du}}    & {~=~}    &{2 \left[\frac{u^{3/2}}{3/2}~+~C_1 \right]~=~\frac{4 u^{3/2}}{3}}~+~C_2    \\
{~\color{magenta}    2    }    &{{}}    &{{}}    & {~=~}    &{\frac{4(x^2\,+\,x\,+\,1)^{3/2}}{3}~+~C}    \\
\end{array}}$

• Note that, the constants C1, C2 etc., can be combined into a single constant C because, all constants, when differentiated, will give zero only.

Part (ii):
1. The given expression can be rearranged as follows:

$\small{\begin{array}{ll} {~\color{magenta}    1    }    &{{}}    &{\frac{1}{1\,-\,\tan x}}    & {~=~}    &{\frac{1}{1\,-\,(\sin x / \cos x)}}    \\
{~\color{magenta}    2    }    &{{}}    &{{}}    & {~=~}    &{\frac{\cos x}{\cos x\,-\,\sin x}}    \\
{~\color{magenta}    3    }    &{{}}    &{{}}    & {~=~}    &{\frac{\cos x}{\sin (\pi/2 \,-\, x)\,-\,\sin x}}    \\
{~\color{magenta}    4    }    &{{}}    &{{}}    & {~=~}    &{\frac{\cos x}{2 \cos(\pi/4) \sin(\pi/4\,-\, x)}}    \\
{~\color{magenta}    5    }    &{{}}    &{{}}    & {~=~}    &{\frac{\cos x}{\sqrt{2} \sin(\pi/4 \,-\, x)}}    \\
\end{array}}$                           

• Derivative of (π/4 − x) w.r.t x is −1.
• So we put u = (π/4 −x)
⇒ $\small{\frac{du}{dx}~=~-1}$
⇒ −dx = du
• Also, since u = (π/4 −x), we get: x = π/4 − u
2. So we want:

$\small{\begin{array}{ll} {~\color{magenta}    1    }    &{{}}    &{\int{\left[\frac{(-1)(-1)\cos x}{\sqrt{2} \sin(\pi/4 \,-\, x)}\right] \, dx}}    & {~=~}    &{\int{\left[\frac{-\cos (\pi/4 \,-\, u)}{\sqrt{2} \sin u}\right] \, du}}    \\
{~\color{magenta}    2    }    &{{}}    &{{}}    & {~=~}    &{\int{\left[\frac{-\cos (\pi/4) \cos u ~-~\sin (\pi/4) \sin u}{\sqrt{2} \sin u}\right] \, du}}    \\
{~\color{magenta}    3    }    &{{}}    &{{}}    & {~=~}    &{\int{\left[\frac{-(1/\sqrt 2) \cos u ~-~(1/\sqrt 2)\sin u }{\sqrt{2} \sin u}\right] \, du}}    \\
{~\color{magenta}    4    }    &{{}}    &{{}}    & {~=~}    &{\int{\left[\frac{-(1/\sqrt 2) \cot u~-~(1/\sqrt 2) }{\sqrt{2}}\right] \, du}}    \\
{~\color{magenta}    5    }    &{{}}    &{{}}    & {~=~}    &{\int{\left[\frac{-(1/\sqrt 2)(\cot u ~+~1)}{\sqrt{2}}\right] \, du}}    \\
{~\color{magenta}    6    }    &{{}}    &{{}}    & {~=~}    &{\int{\left[\frac{-(1~+~\cot u)}{2}\right] \, du}}    \\
\end{array}}$

• This integration can be done as shown below:

$\small{\begin{array}{ll} {~\color{magenta}    1    }    &{{}}    &{\int{\left[\frac{-1~-~\cot u}{2}\right] \, du}}    & {~=~}    &{\int{\left[\frac{-1}{2}\right] \, du}~-~\int{\left[\frac{\cot u}{2}\right] \, du}}    \\
{~\color{magenta}    2    }    &{{}}    &{{}}    & {~=~}    &{\frac{-1}{2} \int{\left[1 \right] \, du}~-~\frac{1}{2} \int{\left[\cot u \right] \, du}}    \\
{~\color{magenta}    3    }    &{{}}    &{{}}    & {~=~}    &{\frac{-1}{2} \left[u\,+\,C_1 \right]~-~\frac{1}{2} \left[\log |\sin u |\,+\, C_2 \right]}    \\
{~\color{magenta}    4    }    &{{}}    &{{}}    & {~=~}    &{-\frac{1}{2} \left[(\pi/4)\,-\,x\,+\,C_1 \right]~-~\frac{1}{2} \left[\log |\sin ((\pi/4)\,-\,x) |\,+\, C_2 \right]}    \\
{~\color{magenta}    5    }    &{{}}    &{{}}    & {~=~}    &{\frac{1}{2} \left[x\,-\,(\pi/4)\,-\,C_1 \right]~+~\frac{1}{2} \left[-\log |\sin ((\pi/4)\,-\,x) |\,-\, C_2 \right]}    \\
{~\color{magenta}    6    }    &{{}}    &{{}}    & {~=~}    &{\frac{1}{2} \left[x\,+\,C_3 \right]~+~\frac{1}{2} \left[-\log |\sin ((\pi/4)\,-\,x) |\,+\, C_4 \right]}    \\
{~\color{magenta}    7    }    &{{}}    &{{}}    & {~=~}    &{\frac{1}{2} \left[x\,+\,C_3 \right]~+~\frac{1}{2} \left[-\log \left|\sin (\pi/4) \, \cos x~-~\cos (\pi/4)  \,\sin x \right |\,+\, C_4 \right]}    \\
{~\color{magenta}    8    }    &{{}}    &{{}}    & {~=~}    &{\frac{1}{2} \left[x\,+\,C_3 \right]~+~\frac{1}{2} \left[-\log \left|(1/\sqrt 2) \, \cos x ~-~  (1/\sqrt 2) \,\sin x \right |\,+\, C_4 \right]}    \\
{~\color{magenta}    9    }    &{{}}    &{{}}    & {~=~}    &{\frac{1}{2} \left[x\,+\,C_3 \right]~+~\frac{1}{2} \left[-\log \left|(1/\sqrt 2)(\cos x ~-~\sin x)  \right |\,+\, C_4 \right]}    \\
{~\color{magenta}    {10}    }    &{{}}    &{{}}    & {~=~}    &{\frac{1}{2} \left[x\,+\,C_3 \right]~+~\frac{1}{2} \left[-\log (1/\sqrt 2)~-~ \log \left|(\cos x ~-~\sin x)  \right |\,+\, C_4 \right]}    \\
{~\color{magenta}    {11}    }    &{{}}    &{{}}    & {~=~}    &{\frac{1}{2} \left[x\,+\,C_3 \right]~+~\frac{1}{2} \left[-\log \left|(\cos x ~-~\sin x)  \right |\,+\, C_5 \right]}    \\
{~\color{magenta}    {12}    }    &{{}}    &{{}}    & {~=~}    &{\frac{x}{2}\,+\,\frac{C_3}{2}~-~\frac{\log \left|(\cos x ~-~\sin x)  \right |}{2}\,+\,\frac{C_5}{2}}    \\
{~\color{magenta}    {13}    }    &{{}}    &{{}}    & {~=~}    &{\frac{x}{2}\,-\,\frac{\log \left|(\cos x ~-~\sin x)  \right |}{2}\,+\,C}    \\
\end{array}}$                            
                           

• Note that, the constants C1, C2, C3 etc., can be combined into a single constant C because, all constants, when differentiated, will give zero only.

Part (iii):
1. The given expression can be rearranged as follows:

$\small{\begin{array}{ll} {~\color{magenta}    1    }    &{{}}    &{\frac{1}{1\,+\,\cot x}}    & {~=~}    &{\frac{1}{1\,+\,(\cos x / \sin x)}}    \\
{~\color{magenta}    2    }    &{{}}    &{{}}    & {~=~}    &{\frac{\sin x}{\sin x\,+\,\cos x}}    \\
{~\color{magenta}    3    }    &{{}}    &{{}}    & {~=~}    &{\frac{\sin x}{\cos (\pi/2 \,-\, x)\,+\,\cos x}}    \\
{~\color{magenta}    4    }    &{{}}    &{{}}    & {~=~}    &{\frac{\sin x}{2 \cos(\pi/4) \cos(\pi/4\,-\, x)}}    \\
{~\color{magenta}    5    }    &{{}}    &{{}}    & {~=~}    &{\frac{\sin x}{\sqrt{2} \cos(\pi/4 \,-\, x)}}    \\
\end{array}}$                           

• Derivative of (π/4 −x) w.r.t x is −1.
• So we put u = (π/4 −x)
⇒ $\small{\frac{du}{dx}~=~-1}$
⇒ −dx = du
• Also, since u = (π/4 −x), we get: x = π/4 − u
2. So we want:

$\small{\begin{array}{ll} {~\color{magenta}    1    }    &{{}}    &{\int{\left[\frac{(-1)(-1)\sin x}{\sqrt{2} \cos(\pi/4 \,-\, x)}\right] \, dx}}    & {~=~}    &{\int{\left[\frac{-\sin (\pi/4 \,-\, u)}{\sqrt{2} \cos u}\right] \, du}}    \\
{~\color{magenta}    2    }    &{{}}    &{{}}    & {~=~}    &{\int{\left[\frac{-\sin (\pi/4) \cos u ~+~\cos (\pi/4) \sin u}{\sqrt{2} \cos u}\right] \, du}}    \\
{~\color{magenta}    3    }    &{{}}    &{{}}    & {~=~}    &{\int{\left[\frac{-(1/\sqrt 2) \cos u ~+~(1/\sqrt 2)\sin u }{\sqrt{2} \cos u}\right] \, du}}    \\
{~\color{magenta}    4    }    &{{}}    &{{}}    & {~=~}    &{\int{\left[\frac{-(1/\sqrt 2) ~+~(1/\sqrt 2) \tan u }{\sqrt{2}}\right] \, du}}    \\
{~\color{magenta}    5    }    &{{}}    &{{}}    & {~=~}    &{\int{\left[\frac{-(1/\sqrt 2)(1~-~\tan u)}{\sqrt{2}}\right] \, du}}    \\
{~\color{magenta}    6    }    &{{}}    &{{}}    & {~=~}    &{\int{\left[\frac{-(1~-~\tan u)}{2}\right] \, du}}    \\
\end{array}}$

• This integration can be done as shown below:

$\small{\begin{array}{ll} {~\color{magenta}    1    }    &{{}}    &{\int{\left[\frac{-1~+~\tan u}{2}\right] \, du}}    & {~=~}    &{\int{\left[\frac{-1}{2}\right] \, du}~+~\int{\left[\frac{\tan u}{2}\right] \, du}}    \\
{~\color{magenta}    2    }    &{{}}    &{{}}    & {~=~}    &{\frac{-1}{2} \int{\left[1 \right] \, du}~+~\frac{1}{2} \int{\left[\tan u \right] \, du}}    \\
{~\color{magenta}    3    }    &{{}}    &{{}}    & {~=~}    &{\frac{-1}{2} \left[u\,+\,C_1 \right]~+~\frac{1}{2} \left[-\log |\cos u |\,+\, C_2 \right]}    \\
{~\color{magenta}    4    }    &{{}}    &{{}}    & {~=~}    &{-\frac{1}{2} \left[(\pi/4)\,-\,x\,+\,C_1 \right]~+~\frac{1}{2} \left[-\log |\cos ((\pi/4)\,-\,x) |\,+\, C_2 \right]}    \\
{~\color{magenta}    5    }    &{{}}    &{{}}    & {~=~}    &{\frac{1}{2} \left[x\,-\,(\pi/4)\,-\,C_1 \right]~+~\frac{1}{2} \left[-\log |\cos ((\pi/4)\,-\,x) |\,+\, C_2 \right]}    \\
{~\color{magenta}    6    }    &{{}}    &{{}}    & {~=~}    &{\frac{1}{2} \left[x\,+\,C_3 \right]~+~\frac{1}{2} \left[-\log |\cos ((\pi/4)\,-\,x) |\,+\, C_2 \right]}    \\
{~\color{magenta}    7    }    &{{}}    &{{}}    & {~=~}    &{\frac{1}{2} \left[x\,+\,C_3 \right]~+~\frac{1}{2} \left[-\log \left|\cos (\pi/4) \, \cos x~+~\sin (\pi/4)  \,\sin x \right |\,+\, C_2 \right]}    \\
{~\color{magenta}    8    }    &{{}}   &{{}}    & {~=~}    &{\frac{1}{2} \left[x\,+\,C_3 \right]~+~\frac{1}{2} \left[-\log \left|(1/\sqrt 2) \, \cos x ~+~  (1/\sqrt 2) \,\sin x \right |\,+\, C_2 \right]}    \\
{~\color{magenta}    9    }    &{{}}    &{{}}    & {~=~}    &{\frac{1}{2} \left[x\,+\,C_3 \right]~+~\frac{1}{2} \left[-\log \left|(1/\sqrt 2)(\cos x ~+~\sin x)  \right |\,+\, C_2 \right]}    \\
{~\color{magenta}    {10}    }    &{{}}    &{{}}    & {~=~}    &{\frac{1}{2} \left[x\,+\,C_3 \right]~+~\frac{1}{2} \left[-\log (1/\sqrt 2)~-~ \log \left|(\cos x ~-~\sin x)  \right |\,+\, C_2 \right]}    \\
{~\color{magenta}    {11}    }    &{{}}    &{{}}    & {~=~}    &{\frac{1}{2} \left[x\,+\,C_3 \right]~+~\frac{1}{2} \left[-\log \left|(\cos x ~+~\sin x)  \right |\,+\, C_4 \right]}    \\
{~\color{magenta}    {12}    }    &{{}}    &{{}}    & {~=~}    &{\frac{x}{2}\,+\,\frac{C_3}{2}~-~\frac{\log \left|(\cos x ~+~\sin x)  \right |}{2}\,+\,\frac{C_4}{2}}    \\
{~\color{magenta}    {13}    }    &{{}}    &{{}}    & {~=~}    &{\frac{x}{2}\,-\,\frac{\log \left|(\cos x ~+~\sin x)  \right |}{2}\,+\,C}    \\
\end{array}}$                           
                           

• Note that, the constants C1, C2, C3 etc., can be combined into a single constant C because, all constants, when differentiated, will give zero only.

Part (iv):
1. The given expression can be rearranged as follows:
$\small{\frac{1}{x\,+\, x \log x}~=~\frac{1}{x(1\,+\, \log x)}}$                     

• Derivative of (1+log x) w.r.t x is: (0+1/x) = 1/x.
• So we put u = 1+ log x
⇒ $\small{\frac{du}{dx}~=~\frac{1}{x}}$
⇒ $\small{du~=~\frac{1}{x} {dx}}$

2. So we want:

$\small{\begin{array}{ll} {~\color{magenta}    1    }    &{{}}    &{\int{\left[\frac{1}{x\,+\, x \log x}\right] \, dx}}    & {~=~}    &{\int{\left[\frac{1}{x(1\,+\, \log x)}\right] \, dx}}    \\
{~\color{magenta}    2    }    &{{}}    &{{}}    & {~=~}    &{\int{\left[\frac{1}{u}\right] \, du}}    \\
\end{array}}$

• This integration can be done as shown below:

$\small{\begin{array}{ll} {~\color{magenta}    1    }    &{{}}    &{\int{\left[\frac{1}{u}\right] \, du}}    & {~=~}    &{\int{\left[\frac{1}{x(1\,+\, \log x)}\right] \, dx}}    \\
{~\color{magenta}    2    }    &{{}}    &{{}}    & {~=~}    &{\int{\left[\frac{1}{u}\right] \, du}}    \\
{~\color{magenta}    3    }    &{{}}    &{{}}    & {~=~}    &{\log|(1\,+\, \log x)|~+~C}    \\
\end{array}}$


The link below gives a few more solved examples:

Exercise 23.2


In the next section, we will see a few more solved examples.

Previous

Contents

Next

Copyright©2025 Higher secondary mathematics.blogspot.com

No comments:

Post a Comment